Castration-resistant prostate cancer monitoring by cell-free circulating biomarkers - Chrenková, Eva; Študentová, Hana; Holá, Kateřina; Kahounová, Zuzana; Hendrychová, Romana; Souček, Karel; Bouchal, Jan (Frontiers in Oncology, 2024)
BackgroundProstate cancer is the second leading cause of male cancer-related deaths in Western countries, which is predominantly attributed to the metastatic castration-resistant stage of the disease (CRPC). There is an urgent need for better prognostic and predictive biomarkers, particularly for androgen receptor targeted agents and taxanes.MethodsWe have searched the PubMed database for original articles and meta-analyses providing information on blood-based markers for castration-resistant prostate cancer monitoring, risk group stratification and prediction of therapy response.ResultsThe molecular markers are discussed along with the standard clinical parameters, such as prostate specific antigen, lactate dehydrogenase or C-reactive protein. Androgen receptor (AR) alterations are commonly associated with progression to CRPC. These include amplification of AR and its enhancer, point mutations and splice variants. Among DNA methylations, a novel 5-hydroxymethylcytosine activation marker of TOP2A and EZH2 has been identified for the aggressive disease. miR-375 is currently the most promising candidate among non-coding RNAs and sphingolipid analysis has recently emerged as a novel approach.ConclusionsThe promising biomarkers have the potential to improve the care of metastatic prostate cancer patients, however, they need further validation for routine implementation.